1986
DOI: 10.1083/jcb.103.4.1383
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody that blocks the activity of a neurite regeneration-promoting factor: studies on the binding site and its localization in vivo.

Abstract: Abstract. Work from several laboratories has identified a proteoglyean complex secreted by a variety of non-neuronal cells that can promote neurite regeneration when applied to the surface of culture dishes. Using a novel immunization protocol, a monoclonal antibody (INO) was produced that blocks the activity of this outgrowth-promoting factor (Matthew, W. D., and P. H. Patterson, 1983, Cold Spring Harbor Symp. Quant. Biol. 48:625-631). We have used the antibody to analyze the components of the active site an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 41 publications
3
66
0
Order By: Relevance
“…One corollary of these observations is that the neurite-promoting site of native laminin molecules does not seem to be significantly antigenic, antibody inhibition relying either on epitopes provided by the 440-kD A chain close to the site (as discussed for EHS laminin), or by more distant sites when the range of the blockade is increased by the use of secondary antibodies (17). Alternatively, it has been shown that a blocking epitope can be created by the association of laminin with other molecules (7).…”
Section: Antibody Inhibition Of Neurite Outgrowthmentioning
confidence: 99%
“…One corollary of these observations is that the neurite-promoting site of native laminin molecules does not seem to be significantly antigenic, antibody inhibition relying either on epitopes provided by the 440-kD A chain close to the site (as discussed for EHS laminin), or by more distant sites when the range of the blockade is increased by the use of secondary antibodies (17). Alternatively, it has been shown that a blocking epitope can be created by the association of laminin with other molecules (7).…”
Section: Antibody Inhibition Of Neurite Outgrowthmentioning
confidence: 99%
“…In almost all cases, LN expression appears to be transient, occurring at high levels during periods of axonal growth and, at least, in the central nervous system, diminishing later in development. Two notable exceptions are the continued expression of LN isoforms in the basal lamina of peripheral nerve (Chiu et al 1986) and the optic nerves of goldfish (Hopkins et al 1985, Liesi 1985, two favorable sites in the adult for either continued axonal growth or nerve regeneration. In contrast to studies on cell migration, surprisingly few attempts have been made to use antibodies or other reagents to interfere with axonal growth.…”
Section: Ecm Regulation Of Cell Migration and Axonal Guidancementioning
confidence: 99%
“…The INO antibody was isolated as an inhibitor of the activity of LN-containing neurite outgrowth factors (Matthew & Patterson 1983). It clearly binds an epitope associated with LN-heparan sulfate complexes (Chiu et al 1986). It also inhibits axonal extension on sections of the peripheral nerve where merosin, B1, and B2 are the major visible LN subunits (Sandrock & Matthew 1987b, Sanes et al 1990.…”
Section: Ecm Regulation Of Cell Migration and Axonal Guidancementioning
confidence: 99%
“…For example, addition of soluble HS disturbs growth of cockroach pioneer axons (Wang and Denburg, 1992) while scission with HS lyases a¡ects retinotectal path¢nding in Xenopus embryos (Walz et al, 1997). HSPG^laminin complexes also modulate neurite outgrowth in vitro including growth promotion and growth inhibition (Lander et al, 1985a,b;Chiu et al, 1986;Hantaz-Ambroise et al, 1987;Mathiessen et al, 1989). For example, whereas monoclonal antibodies to HSPG reduce neurite outgrowth on sciatic nerve in vitro (Sandrock and Matthew, 1985) a Schwannoma-derived HSPG also blocks the neurite-promoting activity of laminin (Muir et al, 1989).…”
Section: Heparan Sulphate Proteoglycansmentioning
confidence: 99%